Investigation of Soft Soil Deformation due to Excavation Work at Sungai Kesang, Johor using PLAXIS 2D - Lading, Cyril Anin; Mohd Fairus bin Yusof, (Recent Trends in Civil Engineering and Built Environment, 2021)
Sungai Kesang is located between the south of Malacca and Johor. The problem started during the construction of the Flood Mitigation Project near the residential house. During excavation work, the nearby house experienced cracked and damaged and it getting worst from time to time. In order to complete the investigation, several cases of excavation with proposed conditions were modelled. The involved conditions were different values of slope angles, different values of ground water level, and different values of surcharge load which represent the house load. There was in total 27 models for this investigation with the usage of Mohr-Coulomb model and Soft Soil model as the material models. The depth of excavation was 4 meter and it took 2 meter per week to excavate stage by stage. Meanwhile, consolidation process took 1 year to complete afterwards. The behaviour of each excavation models were analysed one by one to get the result required. From 27 models, only 9 models were success in the analysis. Other models were failed during phase 1, phase 2 and phase 3. The result obtained from the analysis were compared to find the critical value in terms of settlement and excess pore pressure. This investigation concludes with the best recommendation of excavation in soft soil if the slope angles were less than 30°, the surcharge value is lower and the ground water level is located far from the surface.